2004
DOI: 10.2190/ny8n-d7d7-pvf8-mlcu
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult's Immediate Reaction to a Personal Alcohol Overdose

Abstract: Following an emergency medical transport for alcohol overdose, first-year college students were asked to complete a survey assessing their reactions to the transport experience, their assessment of why they required this emergency response, and plans for future personal alcohol consumption. Transported students who responded to a baseline survey of all first-year students regarding expectations about alcohol are compared to first-year students overall. The 50 first-year transported students did not perceive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Social Learning Theories (SLT; Bandura, 1986) of alcohol use behavior suggest that cognitions (e.g., motivations, expectancies, interpretations) represent the most proximal influences on maladaptive alcohol use behavior, mediating the effects of a variety of more distal environmental and individual difference variables (Maisto, Carey, & Bradizza, 1999). From this perspective, although salient alcohol-related events have been linked to subsequent motivation to change in adults (Apodaca & Schermer, 2001; Dunn et al, 2003; Perreira & Sloan, 2001) and college students (Reis, Harned, & Riley, 2004), it likely is not the consequences themselves that prompt change, but one's cognitive appraisal (i.e., subjective evaluation) of those consequences (Sobell et al, 1993).…”
Section: Subjective Evaluations As Predictors Of Change: Theoretical ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Social Learning Theories (SLT; Bandura, 1986) of alcohol use behavior suggest that cognitions (e.g., motivations, expectancies, interpretations) represent the most proximal influences on maladaptive alcohol use behavior, mediating the effects of a variety of more distal environmental and individual difference variables (Maisto, Carey, & Bradizza, 1999). From this perspective, although salient alcohol-related events have been linked to subsequent motivation to change in adults (Apodaca & Schermer, 2001; Dunn et al, 2003; Perreira & Sloan, 2001) and college students (Reis, Harned, & Riley, 2004), it likely is not the consequences themselves that prompt change, but one's cognitive appraisal (i.e., subjective evaluation) of those consequences (Sobell et al, 1993).…”
Section: Subjective Evaluations As Predictors Of Change: Theoretical ...mentioning
confidence: 99%
“…From this perspective, although salient alcohol-related events have been linked to subsequent motivation to change in adults (Apodaca & Schermer, 2001; Dunn et al, 2003; Perreira & Sloan, 2001) and college students (Reis, Harned, & Riley, 2004), it likely is not the consequences themselves that prompt change, but one’s cognitive appraisal (i.e., subjective evaluation) of those consequences (Sobell et al, 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Barnett et al (2003) reported that young adult Emergency-Room (ER) patients were more likely to be contemplating reducing heavy drinking if they were being treated for an alcohol-related incident, compared with patients with similar patterns of alcohol severity who were not being treated for alcohol-related reasons. In the only identified similar study with college students, Reis et al (2004) assessed first-year students who had been transported to a hospital for alcohol overdose and reported that 83% of these students stated that they planned to decrease the amount they drank.…”
mentioning
confidence: 99%
“…Overall, alcohol-related ambulance calls were strongly associated with patients being underage (i.e., < 21 years) students, consistent with previous findings that freshmen (who are generally underage) constitute a disproportionate number of alcohol-related ED visits 6,8. Evidence suggests that at least half of first-year students who required emergency medical transport admitted to drinking more than they usually drink,19 and that associations between blood alcohol concentrations (BACs) and negative consequences is stronger for lighter drinkers 20. Taken together, it appears that inexperienced drinkers who exceed their usual consumption levels are at greatest risk for ambulance transport.…”
Section: Discussionmentioning
confidence: 99%